Nutraceuticals and COVID‐19: A mechanistic approach toward attenuating the disease complications. Issue 12 (14th October 2022) - Paudel, Keshav Raj; Patel, Vyoma; Vishwas, Sukriti; Gupta, Saurabh; Sharma, Sumit; Chan, Yinghan; Jha, Niraj Kumar; Shrestha, Jesus; Imran, Mohammad; Panth, Nisha; Shukla, Shakti Dhar; Jha, Saurav Kumar; et al.
Abstract: Nutraceuticals have emerged as potential compounds to attenuate the COVID‐19 complications. Precisely, these food additives strengthen the overall COVID treatment and enhance the immunity of a person. Such compounds have been used at a large scale, in almost every household due to their better affordability and easy access. Therefore, current research is focused on developing newer advanced formulations from potential drug candidates including nutraceuticals with desirable properties viz, affordability, ease of availability, ease of administration, stability under room temperature, and potentially longer shelf‐lives. As such, various nutraceutical‐based products such as compounds could be promising agents for effectively managing COVID‐19 symptoms and complications. Most importantly, regular consumption of such nutraceuticals has been shown to boost the immune system and prevent viral infections. Nutraceuticals such as vitamins, amino acids, flavonoids like curcumin, and probiotics have been studied for their role in the prevention of COVID‐19 symptoms such as fever, pain, malaise, and dry cough. In this review, we have critically reviewed the potential of various nutraceutical‐based therapeutics for the management of COVID‐19. We searched the information relevant to our topic from search engines such as PubMed and Scopus using COVID‐19, nutraceuticals, probiotics, and vitamins as a keyword. Any scientific literature published in a language other than English was excluded. Practical applications: Nutraceuticals possess both nutritional values and medicinal properties. They can aid in the prevention and treatment of diseases, as well as promote physical health and the immune system, normalizing body functions, and improving longevity. Recently, nutraceuticals such as probiotics, vitamins, polyunsaturated fatty acids, trace minerals, and medicinal plants have attracted considerable attention and are widely regarded as potential alternatives to current therapeutic options for the effective management of various diseases, including COVID‐19. Abstract : Regular consumption of such nutraceuticals has been shown to boost the immune system and prevent viral infections. Nutraceuticals such as vitamins, amino acids, flavonoids like curcumin, and probiotics have been studied for their beneficial effects in the prevention of COVID‐19 symptoms such as fever, pain, malaise, and dry cough. As such, various nutraceutical‐based products such as compounds could be promising agents for the effective management of COVID‐19 symptoms and complications.